Heart Rate Variability’s Association with Positive and Negative Affect in Daily Life: An Experience Sampling Study with Continuous Daytime Electrocardiography over Seven Days - Justin Hachenberger; Yu-Mei Li; Michael Siniatchkin; Katharin Hermenau; Sebastian Ludyga; Sakari Lemola (Sensors, 2023)
Heart rate variability has been found to be related to emotional processing and emotional responses. Studies that investigated these relationships were mostly lab-based or cross-sectional. Only limited research used intensive longitudinal data, in particular investigating within-individual processes in real-life settings. This study addresses the applicability of ambulatory-assessed electrocardiograms in combination with the experience sampling methodology by investigating the associations of various HRV measures with affective states on within- and between-individual levels. A total of 26 participants aged 18–29 years (23 females) wore electrocardiograms continuously for seven days. The participants received seven prompts per day and answered questions about their affective wellbeing. The heart rate and heart rate variability measures differed between body positions and activity classes. The heart rate and ratio of low-to-high-frequency heart rate variability were consistently associated with positive affect on a within-individual (state-like) level. These associations were mainly driven by the items of feeling “enthusiastic” and “happy”. No associations were found with negative affect. Overall, we found evidence that the dominance of the sympathetic nervous system over the parasympathetic nervous system was associated with higher levels of positive affect on a within-individual (state-like) level. Suggestions for the application of ambulatory electrocardiogram assessment in the study of the association between autonomous nervous system activity and ecological momentary assessment-based variables are discussed.